Comparison of treatment of severe rheumatoid arthritis patients with biological agents and JAK-STAT inhibitors. An extension study - Małgorzata Wisłowska (Rheumatology)
Introduction This study compared treatment with biologic agents and Janus kinase inhibitors (JAKi) in combination with methotrexate (MTX) for rheumatoid arthritis (RA) in a real-world setting at a large center in Poland. There is a persistent shortage of such studies, and illustrating the switching of medications in search of a suitable way of treatment for a given patient is a crucial step towards future personalized therapy.